Effect of Prebiotic, Probiotic, and Enzyme Supplementation on Gut Fermentation, Markers of Inflammation and Immune Response in Individuals with GI Symptoms (P20-024-19). (13th June 2019) - Webb, Kaitlyn; Peterson, Jonathan; Fox, Sean; Chandley, Michelle; Phillips, Kenneth; Chakraboty, Ranjan; Collins, Charles; Johnson, Michelle; Clark, W Andrew
Abstract: Objectives: Chronic gastrointestinal distress (GID) effects up to 33.8% of people and results in over 15 million outpatient visits in the US annually. Currently, probiotic and prebiotic supplements are recommended by physicians, dietitians, and other healthcare providers to normalize GI function and to mitigate symptoms associated with certain disease states. GlutenShield (GS) is a commercially available nutritional supplement designed to contain an appropriate balance of pre- and probiotics as well as digestive enzymes to improve symptoms associated with GID. The aim of this study was to determine the tolerance to and/or benefits of GS supplementation on adults with GID. Methods: This was a partially blinded pilot study in which all subjects completed a 2-week washout and were then randomized to receive GS or the placebo 3 times/day with meals. Participants completed a pre-treatment FFQ as well as a pre- and post-treatment GID questionnaire, POMS questionnaire, blood draw, and stool sample. Results: No differences between placebo and treatment groups were found for serum inflammatory cytokines or fecal volatile fatty acids (area % or concentration) ( P  > 0.05). A significant reduction in IgG2 was observed in the GS group (7110.4 vs 4185.56; P  = 0.008) as well as a significant reduction in self-reported bloating ( P  = 0.038) and approaching significant reduction in total GID ( P  = 0.083). Fecal insoluble dietary fiber (IDF) percentage significantly increased in the placebo group ( P  = 0.012), with no change in the GS group ( P  > 0.05). Conclusions: Research findings suggest that GS was well tolerated and perceived to be beneficial compared to placebo; however, further research is needed to identify the specific patient population of GID patients who could most benefit from GS supplementation. Future analysis of microbiome data of subjects could provide additional insight. Clinical trial ID: NCT03403387. Funding Sources: ETSU (CCRHS, Dean's Research Enhancement Award and CPH, Health Sciences Funding) and Shield Nutraceuticals, LLC.